(untitled) (Revista Apotheke, 2025)
The goal of this article is to investigate the contributions of traditional Brazilian games and plays in the education of the artist, introduced in such a way as to challenge consolidated assumptions in the training of artists in the Brazilian university scene. With the undergraduate course in Arts at the Institute of Art and Social Communication (IACS) at UFF, Niterói, as a locus for experimental work, these pedagogical practices have been applied through the course Proposals with Human and Environmental Interactions, offered to newcomers to the undergraduate course. By introducing plays and games as collective practices, the objective is to challenge the notion that the artist needs to keep themselves isolated in the world, closed off in their own universe, as an indispensable condition for the creative process. With the collaborative practices of traditional plays and games (shuttlecock, hopscotch, cat bed, peg-leg, among others) the aim is, through playfulness and participation, to intervene in the artist’s training processes, stimulating actions and situations that are guided by the notions of exchanging and sharing.